Banishing bureaucracy. The five strategies for reinventing government - OSBORNE, David (Addison-Wesly Pub, 1991)
David Osborne's 1992 bestseller, Reinventing Government, was a landmark book that identified ten principles characteristic of innovative, entrepreneurial, 21st century public organizations and governance. This essential sequel goes one step further, outlining five strategies that have the power to transform public systems and organizations into such organizations, thereby achieving dramatic increases in effectiveness, efficiency, adaptability, and capacity to innovate. In an age of disillusionment with public service, Banishing Bureaucracy offers inspiring stories of organizations that really work and provides specific recipes for effective change. Here is a road map by which reinventors can actually make "reinvention" work.